A differential pumping system to temporarily seal a leaking, rotatable ConFlat flange. (January 2018) - Chan, C.K.; Chang, C.C.; Yang, I.C.; Shueh, C.; Kuan, C.K.; Sheng, Albert; Wu, L.H.
Abstract: A differential pumping system was developed to seal a vacuum leak located between a rotatable ConFlat flange and a section gate valve (SGV). This system can create a vacuum surrounding and isolating the leaking area so as to reduce the leak rate across the leaking paths by four orders of magnitude. Such a differential pumping system has been used in the TLS storage ring (SR) vacuum systems to seal this leak and the beam lifetime could thereby be improved from 350 to 430 min at 360 mA. Highlights: A differential pumping system was developed to seal a leaking rotatable ConFlat flange. This system can reduce the leak rate across the leaking paths by four orders of magnitude. A guard vacuum around the leak of about 8.2 × 10 –2 can be achieved.